Household Food Security: Project results for “His and Hers, time and income: how intra-household dynamics impact nutrition in agricultural households” - Lopera, Diana Carolina; González, Carolina; Twyman, Jennifer; Useche, Pilar; Talsma, Elise F. (International Center for Tropical Agriculture, 2019)
This Info Note considers three metrics widely used in development projects due to their ease of implementation: Household Dietery Diversity Score (HDDS), Months of Adequate Household Food Provisioning (MAHFP) and Household Food Insecurity Access Scale (HFIAS), which act to principally evaluate the component of access in households. The metrics are applied to a sample of Guatemalan agricultural households. This application is framed within the project “His and Hers, time and income: How intra-household dynamics impact nutrition in agricultural households,” led by the International Center for Tropical Agriculture (CIAT) and the University of Florida with funding from the program Innovative Methods and Metrics for Agriculture and Nutrition Actions (IMMANA)